2004
DOI: 10.1101/gad.1192204
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative functions of the SAGA complex mediated through interaction of Spt8 with TBP and the N-terminal domain of TFIIA

Abstract: A surface that is required for rapid formation of preinitiation complexes (PICs) was identified on the N-terminal domain (NTD) of the RNA Pol II general transcription factor TFIIA. Site-specific photocross-linkers and tethered protein cleavage reagents positioned on the NTD of TFIIA and assembled in PICs identified the SAGA subunit Spt8 and the TFIID subunit Taf4 as located near this surface. In agreement with these findings, mutations in Spt8 and the TFIIA NTD interact genetically. Using purified proteins, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
56
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 53 publications
11
56
2
Order By: Relevance
“…Rather, based on our finding that the spt8⌬ activation defect is suppressed by gcn5⌬, Spt8 appears to inhibit the repressive activity of Gcn5. Previous studies in S. cerevisiae have implicated Spt8 in transcriptional activation by recruitment of TBP (Eisenmann et al 1994;Belotserkovskaya et al 2000;Bhaumik and Green 2002;Warfield et al 2004;Sermwittayawong and Tan 2006;Laprade et al 2007). It is not clear how such an activity fits with our results and raises the possibility of other mechanisms by which Spt8 can control transcription.…”
Section: Saga and S Pombe Sexual Differentiation Genes And Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, based on our finding that the spt8⌬ activation defect is suppressed by gcn5⌬, Spt8 appears to inhibit the repressive activity of Gcn5. Previous studies in S. cerevisiae have implicated Spt8 in transcriptional activation by recruitment of TBP (Eisenmann et al 1994;Belotserkovskaya et al 2000;Bhaumik and Green 2002;Warfield et al 2004;Sermwittayawong and Tan 2006;Laprade et al 2007). It is not clear how such an activity fits with our results and raises the possibility of other mechanisms by which Spt8 can control transcription.…”
Section: Saga and S Pombe Sexual Differentiation Genes And Developmentmentioning
confidence: 99%
“…Second, Spt3 and Spt8 recruit the general factor TATA-binding protein (TBP) to certain promoters (Dudley et al 1999;Green 2001, 2002;Larschan and Winston 2001). Spt3 and Spt8 also have been shown to negatively regulate the recruitment of TBP (Belotserkovskaya et al 2000;Yu et al 2003;Warfield et al 2004). Third, Ubp8 is a histone deubiquitylase for histone H2B at K123 (Henry et al 2003; K.K.…”
mentioning
confidence: 99%
“…Gene expression studies have also shown that Gcn5 and subunits of the SAGA TBP-binding module have opposing roles; S. cerevisiae SPT3 and GCN5 mutations were found to have opposite effects in transcriptional regulation of the HO and STE11 genes (Yu et al 2003;Helmlinger et al 2008), although it is possible that some of these phenotypes are due to indirect effects. SAGA can also repress basal expression of some genes in vitro and in vivo (Belotserkovskaya et al 2000;Warfield et al 2004).…”
Section: Saga Organization and Tbp Bindingmentioning
confidence: 99%
“…These include NC2, TFIIA, TFIIB (77), Mbf1p (78), Spt3p, Spt8p, and Ada1p subunits of SAGA (79,80), TFIID Taf1p and TAND (58,59,81,82), Med8p and Med20p subunits of Mediator (83), Brf1p subunit of TFIIIB (84), TAF I 48 subunit of SL1 (85), N-terminal domain of Mot1p (86), SNAP190 subunit of SNAP C (87), and the NOT complex (88). Interestingly, many of these TBP-targeted factors both activate and repress transcription (76).…”
Section: Discussionmentioning
confidence: 99%